2006
DOI: 10.3189/172756406781812410
|View full text |Cite
|
Sign up to set email alerts
|

Atmosphere-to-snow-to-firn transfer of NO3 on Ürümqi glacier No. 1, eastern Tien Shan, China

Abstract: In order to investigate the relationship between atmospheric nitrate and nitrate records in glacial snow and firn, nitrate was investigated in atmospheric aerosol, surface snow and the snow–firn pack on Ürümqi glacier No. 1 , eastern Tien Shan, China, from September 2002 to September 2004. The study found that vertical nitrate stratigraphy in the upper snowpack is formed during the winter by dry deposition and compaction and sublimation of the snowpack. During the summer the snowpack nitrate is redistributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
1
12
0
1
Order By: Relevance
“…Higher contributions of NO − 3 in aerosols than snowpits cannot be simply concluded as an increase in anthropogenic aerosol concentrations in this region between 1989 and 2009, due to the complicated air-to-snow-tofirn transfer processes. According to the study by Zhao et al (2006), nitrate was found to be highly mobile in the snowpack, and appeared to be preferentially leached downward into the ice layer, thus, concentrations of NO − 3 seemed lower in snowpits. Due to the complicated transfer processes, only use the NO − 3 in snowpits cannot reflect whether there were anthropogenic pollutions affecting this region in 1989.…”
Section: Comparison With Data Of the Previous Study And Other Areasmentioning
confidence: 94%
“…Higher contributions of NO − 3 in aerosols than snowpits cannot be simply concluded as an increase in anthropogenic aerosol concentrations in this region between 1989 and 2009, due to the complicated air-to-snow-tofirn transfer processes. According to the study by Zhao et al (2006), nitrate was found to be highly mobile in the snowpack, and appeared to be preferentially leached downward into the ice layer, thus, concentrations of NO − 3 seemed lower in snowpits. Due to the complicated transfer processes, only use the NO − 3 in snowpits cannot reflect whether there were anthropogenic pollutions affecting this region in 1989.…”
Section: Comparison With Data Of the Previous Study And Other Areasmentioning
confidence: 94%
“…Two apparent high peaks (Figure 3a (Figure 3) from 19 March to 17 April. This was mainly related to small precipitation events, low temperatures (always below zero), and weak evaporation during this period, which enabled post-depositional processes such as sublimation and dry deposition to become more dominant [40,41]. Especially, little melt occurred under the condition, which partially contributed to high values of Ca 2+ and other major ions in the surface of the snowpit.…”
Section: Elution Processmentioning
confidence: 96%
“…The sampling site, which is also known as the PGPI site, is in the percolation zone at the east branch of UG1 at an altitude of 4 130 m a.s.l. (Dong et al, 2010;Li Z Q et al, 2008Li Z Q et al, , 2006Wang et al, 2008Wang et al, , 2006Li X Y et al, 2007;Zhao et al, 2006). There is no direct wintertime exposure to sunshine due to the shadowing effect of the mountain ridges at the sampling site .…”
Section: Site Descriptionmentioning
confidence: 92%